THE TRANSITION FROM ACTIVE LESIONS TO STRUCTURAL CHANGES ON SACROILIAC MRI AND ITS ASSOCIATED FACTORS - Kalyoncu, U.; Ayan, G.; Kilic, L.; Atagunduz, P.; Akar, S.; Bilge, N. S. Yasar; Kiraz, S. (Bmj Publishing Group, 2023)
[Abstract Not Available]
European Congress of Rheumatology (EULAR) -- MAY 31-JUN 03, 2023 -- Milan, ITALY
Keywords: Spondyloarthritis; Real-world evidence; Registries